If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1x = 2x + 3x + -5x Combine like terms: 2x + 3x = 5x 4 + -1x = 5x + -5x Combine like terms: 5x + -5x = 0 4 + -1x = 0 Solving 4 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| -2t=6.3 | | v^2=u^2+2 | | 0.4n=2 | | 27+27x=351-9x | | 2y-7y=40 | | a-5.3=1.1 | | 9=p-8 | | .05x+3.11=.03x+3.03 | | 4a(5-3a)= | | 2.8+x=4.9 | | 3X+2(3X+2)=28 | | 954(3)=p | | 9a-5=2a | | 8x^3-13=-77 | | .4x-2.3=-1.1 | | 5x-8+3x=-10 | | 16t^2+16t-480=0 | | 6(t-2)=2(9-2f) | | 2s-12+12s=4s-12 | | 0.5(8x-4)=10x-9 | | -3x-152+40x=20 | | 12=.99x+20.76 | | 3(x+17.50)=136.50 | | 0=(x^3)-(x^2)-20 | | X+2=16-28 | | 8(x-1)-2(3x-1)=x-1 | | -5t+5=-5 | | 2-2(5y+7)=2(-6-2)+1 | | 5(g+12)=145 | | 0=x^3-7x^2-9x+63 | | -3c+2=7 | | 20+2x=4x-68 |